Lost-in-the-mall: False memory or false defense?. Issue 1 (2nd January 2019) - Blizard, Ruth A.; Shaw, Morgan
Abstract: False Memory Syndrome (FMS) and Parental Alienation Syndrome (PAS) were developed as defenses for parents accused of child abuse as part of a larger movement to undermine prosecution of child abuse. The lost-in-the-mall study by Dr. Elizabeth Loftus concludes that an entire false memory can be implanted by suggestion. It has since been used to discredit abuse survivors' testimony by inferring that false memories for childhood abuse can be implanted by psychotherapists. Examination of the research methods and findings of the study shows that no full false memories were actually formed. Similarly, PAS, coined by Richard Gardner, is frequently used in custody cases to discredit children's testimony by alleging that the protective parent coached them to have false memories of abuse. There is no scientific research demonstrating the existence of PAS, and, in fact, studies on the suggestibility of children show that they cannot easily be persuaded to provide detailed disclosures of abuse.